Результати перезимівлі гібридів F1, F2 та F3 між Diospyros kaki L. та D. virginiana L. в умовах Південного Степу України у 2005–2006 рр. - Derevaynko, V.N. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2007)
Results of long influence of low temperatures on F1, F2 and F3 hybrids between Diospyros kaki L. and D. virginiana L. in Experimental Farm Novokakhovskoe of Nikita Botanical Garden – National Scientific Center of Ukrainian Academy of Agrarian Sciences are analyzed.